2017
DOI: 10.7554/elife.26014
|View full text |Cite
|
Sign up to set email alerts
|

MicroCT-based phenomics in the zebrafish skeleton reveals virtues of deep phenotyping in a distributed organ system

Abstract: Phenomics, which ideally involves in-depth phenotyping at the whole-organism scale, may enhance our functional understanding of genetic variation. Here, we demonstrate methods to profile hundreds of phenotypic measures comprised of morphological and densitometric traits at a large number of sites within the axial skeleton of adult zebrafish. We show the potential for vertebral patterns to confer heightened sensitivity, with similar specificity, in discriminating mutant populations compared to analyzing individ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 40 publications
1
75
0
Order By: Relevance
“…While these studies have demonstrated the power of X-ray imaging, in most cases the downstream analysis in terms of digital atlas, segmentation and morphometric analysis was not exploited with the exception of Wong et al ., who reported a morphometric CT based analysis of mouse mutant embryos 22 . Semi-automated segmentation of vertebrae has been used for a comparative analysis of mutant and wild type zebrafish 51 . Since our aim was to employ micro-CT data for comparative morphometric analysis of large sample sizes we implemented automated segmentation as a user friendly and fast image analysis.…”
Section: Discussionmentioning
confidence: 99%
“…While these studies have demonstrated the power of X-ray imaging, in most cases the downstream analysis in terms of digital atlas, segmentation and morphometric analysis was not exploited with the exception of Wong et al ., who reported a morphometric CT based analysis of mouse mutant embryos 22 . Semi-automated segmentation of vertebrae has been used for a comparative analysis of mutant and wild type zebrafish 51 . Since our aim was to employ micro-CT data for comparative morphometric analysis of large sample sizes we implemented automated segmentation as a user friendly and fast image analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent advances in μCT-based methods enable detailed and rapid skeletal phenotyping of zebrafish mutants, which often have been resistant to such methodologies ( 24 ). Advances in processing and analysis have now allowed analysis of hundreds of morphological and densitometric traits in large sets of zebrafish skeletal mutants ( 25 ). In this work, we applied systematic collagen analysis with skeletal phenomics to characterize a large set of zebrafish with mutations in type I collagen genes, as seen in patients with different forms of classical OI and EDS, to assess to which extent key features of human type I collagenopathies are recapitulated.…”
mentioning
confidence: 99%
“…The scale was designed according to a pre-defined parameter (air, HU = −1,000, color index = 0) and scanning results (including water and phantoms) to generate the mapping reference between color index (0–255) and Hounsfield units (HUs; in our case, −1,000 to 3,184). The 3D rendering was done by using CTvox software (Bruker microCT, Kontich, Belgium) and the BMD was analyzed by using CTAn software (Bruker microCT, Kontich, Belgium) with the fourth (a Weberian vertebra) or all vertebrae as the region of interest ( Bird & Mabee, 2003 ; Hur et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%